2019
DOI: 10.1029/2018rg000629
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Geomagnetic Field Intensity in Late Quaternary Evolution of Humans and Large Mammals

Abstract: It has long been speculated that biological evolution was influenced by ultraviolet radiation (UVR) reaching the Earth's surface, despite imprecise knowledge of the timing of both UVR flux and evolutionary events. The past strength of Earth's dipole field provides a proxy for UVR flux because of its role in maintaining stratospheric ozone. The timing of Quaternary evolutionary events has become better constrained by fossil finds, improved radiometric dating, use of dung fungi as proxies for herbivore populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 232 publications
(420 reference statements)
1
25
0
Order By: Relevance
“…Present-day studies imply that geomagnetic excursions, e.g. Laschamp excursion (41 to 42 thousand years ago) and excursions identified in sediments of Brunhes Chron (nearly 13 thousand years ago) could have led to a regional extinction of large mammals (Channell and Vigliotti 2019). According to Cooper et al (2021), the Laschamp excursion in combination with the Grand Solar Minima, initiated substantial changes in the concentration and circulation of the atmospheric ozone, increased atmospheric ionisation and ultraviolet (UV) radiation levels, leading to global climate shifts that caused major environmental changes.…”
Section: The Impact Of the Geomagnetic Reversalmentioning
confidence: 99%
See 1 more Smart Citation
“…Present-day studies imply that geomagnetic excursions, e.g. Laschamp excursion (41 to 42 thousand years ago) and excursions identified in sediments of Brunhes Chron (nearly 13 thousand years ago) could have led to a regional extinction of large mammals (Channell and Vigliotti 2019). According to Cooper et al (2021), the Laschamp excursion in combination with the Grand Solar Minima, initiated substantial changes in the concentration and circulation of the atmospheric ozone, increased atmospheric ionisation and ultraviolet (UV) radiation levels, leading to global climate shifts that caused major environmental changes.…”
Section: The Impact Of the Geomagnetic Reversalmentioning
confidence: 99%
“…According to Cooper et al (2021), the Laschamp excursion in combination with the Grand Solar Minima, initiated substantial changes in the concentration and circulation of the atmospheric ozone, increased atmospheric ionisation and ultraviolet (UV) radiation levels, leading to global climate shifts that caused major environmental changes. It was also suggested that those environmental changes could have sparked a chain of events leading to the extinction of large mammals in Australia and Europe, and possibly to the extinction of Homo neanderthalensis (King 1864) and subsequent success of Homo sapiens Linnaeus 1758 (Channell and Vigliotti 2019;Cooper et al 2021). Similarly, large mammals' extinctions in North America and Europe 13 thousand years ago could be linked to geomagnetic excursions identified in sediments of Brunhes Chron.…”
Section: The Impact Of the Geomagnetic Reversalmentioning
confidence: 99%
“…Recent evidence demonstrated that megafauna (including Hominidae) die-offs in North America and Eurasia were associated with geomagnetic field intensity minima ( Channell and Vigliotti, 2019 ). The Neolithic population collapse (~5500 before present (BP) years), which occurred over approximately 500 years in the mid-Holocene (~7000 to 5000 BP), was temporally coupled to the last geomagnetic field intensity minimum ( Shennan et al, 2013 ; Batt et al, 2017 ; Nilsson et al, 2014 ; Riris and Arroyo-Kalin, 2019 ; Warden et al, 2017 ; Li et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Humans are continuously exposed to MFs, which are from natural origin comprising GMF, thunderstorm, solar storms and/or manmade sources such as power transmission lines, factories, MRI and other therapeutic apparatuses, etc 54 . Indeed, MFs as stimuli or deleterious stresses are important phenomena in our surrounding environment, has been associated with the human health modulate the physiological and hemostatic functions of cells especially neural cells and the circadian periods 55,56 . However, the mechanism of these biologic in uencing is not well-established on the cellular behaviors.…”
Section: Discussionmentioning
confidence: 99%